Graphic Materials. How Materiality Affects the Form of Writing and Written Texts - De Angelis, Rossana (E|C, 2023)
In the history of writing, the relationship between the raw materials available (stone, wood, wax, clay, leaves, rags, metals etc.), their transformation to make materials as blocks, boards, layers, papers, bars etc., adapted to inscription (engrave, paint, ink, type etc.), and the tools adopted to inscribe (stylus, brushes, pens, keyboards, screens etc.), shows that the circulation of writing systems and written objects depends on a complex balance between several factors, including material ones. In fact, this materiality interacts both with the enunciative authorities and the enunciative institutions for the production, stabilization and transmission of texts. In this article, we’ll try to understand how the materiality of writings acts in this dynamic.